Game for learning II - Lin, Yuling (Nanyang Technological University, 2022)
Games are being widely used more purposes outside entertainment. There are an increasing number of studies regarding the use of serious games for education. The project attempted to design and build an educational game for the primary and secondary school students to learn two simple topics in astronomy. With the carefully chosen product positioning of a simplistic, cost-effective 2D game that required minimum artwork, the project allowed more space for the designer to practice good game designs, good project management practices, carefully iterated and tested implementations, and detailed user surveys. The game application involves two main mini games, with different in gameplay and methodologies in learning. The project owner also took considerable amount of time to fine tune many features for best user experience. After proper testing and deployment, the project was able to perform intensive user engagements, both online and offline. Meaningful feedbacks were gathered to give ideas of improvements and demonstrate the successfulness of achievements of project objectives. The survey data showed that in both topics, users saw an improvement in their understandings of the topics involved.